Diagnostic and predictive relevance of protein tyrosine phosphatase receptor type C serum levels and rs10919563 variant in rheumatoid arthritis and tumor necrosis factor inhibitor outcomes - A. H. Kamel; A. A. Abbas; M. H. Alosami (Regulatory Mechanisms in Biosystems, 2025)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by the central role of immune dysregulation. There is growing evidence linking the pathophysiology of some autoimmune disorders to protein tyrosine phosphatase receptor typ e C (PTPRC), a crucial modulator of immune cell communication. The current study's objective was to assess the predictive and diagnostic ability of rs10919563 polymorphism and serum PTPRC levels in relation to RA patients' disease activity and tumor necrosis factor (TNF) inhibitor responsiveness. One hundred RA patients and one hundred healthy controls were subjected to case-control analysis. En zyme-linked immunosorbent assa y (ELISA) was used to measure serum PTPRC levels, and TaqMan real-time PCR was used to genotype PTPRC rs10919563. Following six months of TNF inhibitor treatment, scores from the clinical disease activity i ndex (CDAI) were assessed to measure disease activity and medication response. Area under the curve (AUC) = 0.979 indicated very strong diagno s tic performance, and serum PTPRC concentrations were considerably greater in RA patients than in controls. Higher disease activity and a decreased responsiveness to TNF inhibitors were linked to the AA genotype and the A allele of rs10919563. Higher serum levels of PTPRC as well as AA genotype also correlated with higher CDAI scores. In patients with RA, elevated serum levels of PTPRC and polymorphism rs10919563 are linked to high disease activity and poor therapy response. These results support PTPRC's potential clinical use as a RA biomarker for diagnosis, follow-up, and customized treatment.